ANALISIS PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (Studi pada Pengguna Go-Pay pada Aplikasi GO-JEK di Kota Semarang) - Nur Aisah; Budi Sudaryanto (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of customer relationship management and trust on customer loyalty through customer satisfaction of Go-Pay users on the Go-jek application in the city of Semarang. The variables used in this study are customer relationship management and trust as independent variables, customer satisfaction as the intervening variable and customer loyalty as the dependent variable. The population in this study are users of Go-Pay services on the Go-Jek application in the city of Semarang. The number of samples used is as many as 130 respondents. This research uses Structural Equation Modeling (SEM) analysis technique using AMOS analysis tool. The results of this study indicate that customer relationship management has a positive and significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction, customer relationship management has a positive and significant effect on customer loyalty, trust has a positive and significant effect on customer loyalty, and customer satisfaction has a positive effect. and significant to customer loyalty